Prediction of Escape Red Blood Cell Transfusion in Expectantly Managed Women With Acute Anaemia After Postpartum Haemorrhage. Issue 4 (December 2016) - Prick, B.W.; Schuit, E.; Mignini, L.; Jansen, A.J.G.; van Rhenen, D.J.; Steegers, E.A.P.; Mol, B.W.; Duvekot, J.J.
Abstract : ( BJOG . 2015;122(13):1789–1797) Severe postpartum hemorrhage (blood loss of at least 1000 mL) remains a relatively common obstetric complication. In fact, the incidence has been increasing in some developed countries, and the worldwide prevalence has been reported at 1.9%. The purpose of this study was to determine clinical predictors of the need for escape red blood cell (RBC) transfusion (a transfusion administered beyond the acute blood loss phase) in postpartum anemic women who were initially managed expectantly. In addition, the study evaluated whether health-related quality of life (HRQoL) scores provided additional predictive value beyond the clinical predictors determined.